Roadmap to the Inclusion of Lifestyle Medicine in Undergraduate Medical Curriculum in India - Prateek Sudhakar Bobhate; Saurabh RamBihariLal Shrivastava (Journal of the Scientific Society)
Noncommunicable diseases (NCDs) are an ever-growing public health problem globally. Approximately around 40 million deaths are attributed to NCDs. Lifestyle changes and rapid urbanization are the major factors in this rising trend of NCDs, especially in younger age groups. India is facing a double burden of both lifestyle-related disorders as well as communicable diseases. To curb this, the programs and policies have to be targeted mainly toward primordial and primary prevention of the disease simultaneously along with secondary prevention. With the inclusion of lifestyle medicine in the undergraduate medical curriculum in India, healthcare professionals will be better equipped to promote preventive measures and improve patient outcomes in lifestyle-related diseases, and it can be a crucial step toward transforming healthcare delivery and mitigating the impact of lifestyle-related diseases in India.